All-optical generation of antiferromagnetic magnon currents via the magnon circular photogalvanic effect - Bostroem, Emil Vinas; Parvini, Tahereh Sadat; Mciver, James W.; Rubio, Angel; Viola Kusminskiy, Silvia; Sentef, Michael A. (Physical Review B, 2021)
We introduce the magnon circular photogalvanic effect enabled by two-magnon Raman scattering. This provides an all-optical pathway to the generation of directed magnon currents with circularly polarized light in honeycomb antiferromagnetic insulators. The effect is the leading order contribution to magnon photocurrent generation via optical fields. Control of the magnon current by the polarization and angle of incidence of the laser is demonstrated. Experimental detection by sizable inverse spin Hall voltages in platinum contacts is proposed.
CRIS-Team Scopus Importer:2021-09-17

Antiferromagnetic cavity optomagnonics - Parvini, T. S.; Bittencourt, V. A. S. V.; Viola Kusminskiy, Silvia (Physical Review Research, 2020)
Currently there is a growing interest in studying the coherent interaction between magnetic systems and electromagnetic radiation in a cavity, prompted partly by possible applications in hybrid quantum systems. We propose a multimode cavity optomagnonic system based on antiferromagnetic insulators, where optical photons couple coherently to the two homogeneous magnon modes of the antiferromagnet. These have frequencies typically in the THz range, a regime so far mostly unexplored in the realm of coherent interactions, and which makes antiferromagnets attractive for quantum transduction from THz to optical frequencies. We derive the theoretical model for the coupled system, and show that it presents unique characteristics. In particular, if the antiferromagnet presents hard-axis magnetic anisotropy, the optomagnonic coupling can be tuned by a magnetic field applied along the easy axis. This allows us to bring a selected magnon mode into and out of a dark mode, providing an alternative for a quantum memory protocol. The dynamical features of the driven system present unusual behavior due to optically induced magnon-magnon interactions, including regions of magnon heating for a red-detuned driving laser. The multimode character of the system is evident in a substructure of the optomagnonically induced transparency window.
CRIS-Team WoS Importer:2021-01-22

Cavity optomagnonics - Viola Kusminskiy, Silvia (Optomagnonic Structures: Novel Architectures For Simultaneous Control Of Light And Spin Waves, 2021)
In the recent years a series of experimental and theoretical efforts have centered around a new topic: the coherent, cavity-enhanced interaction between optical photons and solid state magnons. The resulting emerging field of Cavity Optomagnonics is of interest both at a fundamental level, providing a new platform to study light-matter interaction in confined structures, as well as for its possible relevance for hybrid quantum technologies. In this chapter, I introduce the basic concepts of Cavity Optomagnonics and review some theoretical developments.
CRIS-Team Scopus Importer:2021-07-16

Design of an optomagnonic crystal: Towards optimal magnon-photon mode matching at the microscale - Graf, Jasmin; Sharma, Sanchar; Huebl, Hans; Viola Kusminskiy, Silvia (Physical Review Research, 2021)
We put forward the concept of an optomagnonic crystal: a periodically patterned structure at the microscale based on a magnetic dielectric, which can co-localize magnon and photon modes. The co-localization in small volumes can result in large values of the photon-magnon coupling at the single quanta level, which opens perspectives for quantum information processing and quantum conversion schemes with these systems. We study theoretically a simple geometry consisting of a one-dimensional array of holes with an abrupt defect, considering the ferrimagnet yttrium iron garnet (YIG) as the basis material. We show that both magnon and photon modes can be localized at the defect, and use symmetry arguments to select an optimal pair of modes in order to maximize the coupling. We show that an optomagnonic coupling in the kHz range is achievable in this geometry, and discuss possible optimization routes in order to improve both coupling strengths and optical losses.
CRIS-Team Scopus Importer:2021-10-08

Dynamical Backaction Magnomechanics - Potts, C. A.; Varga, E.; Bittencourt, V. A. S. V.; Viola Kusminskiy, Silvia; Davis, J. P. (Physical Review X, 2021)
Dynamical backaction resulting from radiation pressure forces in optomechanical systems has proven to be a versatile tool for manipulating mechanical vibrations. Notably, dynamical backaction has resulted in the cooling of a mechanical resonator to its ground state, driving phonon lasing, the generation of entangled states, and observation of the optical-spring effect. In certain magnetic materials, mechanical vibrations can interact with magnetic excitations (magnons) via the magnetostrictive interaction, resulting in an analogous magnon-induced dynamical backaction. In this article, we directly observe the impact of magnon-induced dynamical backaction on a spherical magnetic sample's mechanical vibrations. Moreover, dynamical backaction effects play a crucial role in many recent theoretical proposals; thus, our work provides the foundation for future experimental work pursuing many of these theoretical proposals.Y
CRIS-Team WoS Importer:2021-09-24

Levitating the future: light, magnet, and fiber unite - Chakraborty, Soumya; Wong, Gordon Kwan Leung; Oda, Ferdi; Wachter, Vanessa; Kusminskiy, Silvia Viola; Yokosawa, Tadahiro; Hübner, Sabine; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Distaso, Monica; Russell, Philip St. J.; Joly, Nicolas (Proceedings Volume PC12991, Nanophotonics X, 2024)
We report the first-ever observation of optomagnetically-driven rotation of a magnetic particle, optically levitated inside a chiral hollow-core photonic crystal fibre (HC-PCF). Rotation of the optically biaxial particle causes a change in the transmitted power and ellipticity of a linearly polarised probe beam at 632.8 nm. HC-PCF offers a versatile platform for investigating the optomechanical response of levitated magnetic particle

Magnon heralding in cavity optomagnonics - Bittencourt, Victor A. S. V.; Feulner, Verena; Viola Kusminskiy, Silvia (Physical Review A, 2019)
In the emerging field of cavity optomagnonics, photons are coupled coherently to magnons in solid-state systems. These new systems are promising for implementing hybrid quantum technologies. Being able to prepare Fock states in such platforms is an essential step towards the implementation of quantum information schemes. We propose a magnon-heralding protocol to generate a magnon Fock state by detecting an optical cavity photon. Due to the peculiarities of the optomagnonic coupling, the protocol involves two distinct cavity photon modes. Solving the quantum Langevin equations of the coupled system, we show that the temporal scale of the heralding is governed by the magnon-photon cooperativity and derive the requirements for generating high fidelity magnon Fock states. We show that the nonclassical character of the heralded state, which is imprinted in the autocorrelation of an optical "read" mode, is only limited by the magnon lifetime for small enough temperatures. We address the detrimental effects of nonvacuum initial states, showing that high fidelity Fock states can be achieved by actively cooling the system prior to the protocol.
CRIS-Team WoS Importer:2019-07-23

Magnon-Phonon Quantum Correlation Thermometry - Potts, C. A.; Bittencourt, V. A. S. V.; Viola Kusminskiy, Silvia; Davis, J. P. (Physical Review Applied, 2020)
A large fraction of quantum science and technology requires low-temperature environments such as those afforded by dilution refrigerators. In these cryogenic environments, accurate thermometry can be difficult to implement, expensive, and often requires calibration to an external reference. Here, we theoretically propose a primary thermometer based on measurement of a hybrid system consisting of phonons coupled via a magnetostrictive interaction to magnons. Thermometry is based on a cross-correlation measurement in which the spectrum of back-action driven motion is used to scale the thermomechanical motion, providing a direct measurement of the phonon temperature independent of experimental parameters. Combined with a simple low-temperature compatible microwave cavity readout, this primary thermometer is expected to become a promising alternative for thermometry below 1 K.
CRIS-Team WoS Importer:2020-06-16

Optical signatures of the coupled spin-mechanics of a levitated magnetic microparticle - Wachter, Vanessa; Bittencourt, Victor A. S. V.; Xie, Shangran; Sharma, Sanchar; Joly, Nicolas; Russell, Philip St. John; Marquardt, Florian; Viola Kusminskiy, Silvia (Journal of the Optical Society of America B-Optical Physics, 2021)
We propose a platform that combines the fields of cavity optomagnonics and levitated optomechanics to control and probe the coupled spin-mechanics of magnetic dielectric particles. We theoretically study the dynamics of a levitated Faraday-active dielectric microsphere serving as an optomagnonic cavity, placed in an external magnetic field and driven by an external laser. We find that the optically driven magnetization dynamics induces angular oscillations of the particle with low associated damping. Further, we show that the magnetization and angular motion dynamics can be probed via the power spectrum of the outgoing light. Namely, the characteristic frequencies attributed to the angular oscillations and the spin dynamics are imprinted in the light spectrum by two main resonance peaks. Additionally, we demonstrate that a ferromagnetic resonance setup with an oscillatory perpendicular magnetic field can enhance the resonance peak corresponding to the spin oscillations and induce fast rotations of the particle around its anisotropy axis. (C) 2021 Optical Society of America
Created from Fastlane, WoS look-up

Roadmap on Spin-Wave Computing - Chumak, A. V.; Kabos, P.; Wu, M.; Abert, C.; Adelmann, C.; Adeyeye, A.; Akerman, J.; Aliev, F. G.; Anane, A.; Awad, A.; Back, C. H.; Barman, A.; et al. (IEEE Transactions on Magnetics, 2022)
Magnonics addresses the physical properties of spin waves and utilizes them for data processing. Scalability down to atomic dimensions, operation in the GHz-to-THz frequency range, utilization of nonlinear and nonreciprocal phenomena, and compatibility with CMOS are just a few of many advantages offered by magnons. Although magnonics is still primarily positioned in the academic domain, the scientific and technological challenges of the field are being extensively investigated, and many proof-of-concept prototypes have already been realized in laboratories. This roadmap is a product of the collective work of many authors that covers versatile spin-wave computing approaches, conceptual building blocks, and underlying physical phenomena. In particular, the roadmap discusses the computation operations with Boolean digital data, unconventional approaches like neuromorphic computing, and the progress towards magnon-based quantum computing. The article is organized as a collection of sub-sections grouped into seven large thematic sections. Each sub-section is prepared by one or a group of authors and concludes with a brief description of current challenges and the outlook of further development for each research direction.
CRIS-Team Scopus Importer:2022-02-25
Keywords: computing; data processing; Logic gates; Magnetic domains; magnon; magnonics; Magnonics; Nanoscale devices; Physics; Quantum computing; Spin wave; Three-dimensional displays

Spin cat states in ferromagnetic insulators - Sharma, Sanchar; Bittencourt, Victor A.S.V.; Karenowska, Alexy D.; Viola Kusminskiy, Silvia (Physical Review B, 2021)
Generating nonclassical states in macroscopic systems is a long-standing challenge. A promising platform in the context of this quest are novel hybrid systems based on magnetic dielectrics, where photons can couple strongly and coherently to magnetic excitations, although a nonclassical state therein is yet to be observed. We propose a scheme to generate a magnetization cat state, i.e., a quantum superposition of two distinct magnetization directions, using a conventional setup of a macroscopic ferromagnet in a microwave cavity. Our scheme uses the ground state of an ellipsoid shaped magnet, which displays anisotropic quantum fluctuations akin to a squeezed vacuum. The magnetization collapses to a cat state by either a single photon or a parity measurement of the microwave cavity state. We find that a cat state with two components separated by ∼5ℏ is feasible and briefly discuss potential experimental setups that can achieve it.
CRIS-Team Scopus Importer:2021-04-02